Nilai-Nilai Pendidikan Budi Pekerti dalam Film Bajrangi Bhaijaan - Anggraeni Novita Sari (Academica: Journal of Multidisciplinary Studies, 2018)
AbstractEducation is not just a transfer of knowledge but also looks at the moral side and character. The process of cultivating character can be done through a variety of media. One of the media that can be used as a means of inculcating moral values is film. Films with audio and visual depictions are able to influence someone to act in accordance with the message in the film. In this study, the author examines the Bajrangi Bhaijaan film. The aim of this research is to explore the values of character contained in the film. The method used in this research is the semiotic analysis method. The results of the analysis of the film Bajrangi Bhaijaan show that the film has a lot of moral values. First the caring attitude. Both are devoted to God, as God's creatures. Third is the work ethic or hard work. Fourth love affection. Fifth discipline. Sixth honest, honest attitude will make someone trusted by others. Seventh responsibility, this attitude reflects someone who is able to solve problems and the mandate given to him. Eighth tolerance, this attitude of tolerance is related to the relationship of one human being with another human being. The nine solidarity, the attitude that shows sincerity in a friendship. The ten statements of gratitude,Keywords: Value of character, film